(untitled) (IIUC Business Review, 2026)
In the ever-evolving global business landscape, bolstering technological improvement is vital in organizations’ Accounting Information Systems (AIS). This research explores the dynamic interplay between AIS and organizational effectiveness within the specific context of the ready-made garments (RMG) industry in Chattogram, Bangladesh. The study measured the AIS as financial reporting accuracy, timeliness of decision-making, data security integrity, ease of accessibility, regulatory standards compliance, and user satisfaction. Also, the effectiveness of an organization is measured as cost effectiveness, integration with other systems, decision support, adaptability to change, training and support, and innovation and upgradation from 400 respondents from the RMG on a five-point Likert scale with a purposive sampling approach. The collected response data are classified via factor analysis and validated d with Cronbach’s Alpha value in IBM SPSS Statistics 26. Based on the above classification, a structural equation modeling (SEM) is developed in IBM SPSS AMOS 22 for AIS and organizational effectiveness and validated with convergent and discriminant validity. The study results showed that the practice of AIS significantly contributes to an organization’s effectiveness. Thus, AIS may be applied in the RMG industry to increase decision-making efficiency, simplify processes, and enhance the accuracy of financial reporting. IIUC Business Review, Vol.-13, Issue-1, December 2024, pp. 117-146